Social And Economic Effects of Housing Demand in Foreign Geography: Trabzon - Ceren Ünlü Öztürk; Zeynep Yılmaz Bayram (Coğrafya Dergisi)
The ownership of second homes has moved to the international level due to developments in transportation technologies and the laws of nation states. This has affected cities both positively and negatively. In 2012, the principle of reciprocity, which governs the acquisition of immovable property by citizens of different countries, was abolished in Turkey. Post this, there has been a differentiation in the nationalities of foreigners who purchase housing properties in Turkey and in their preferred cities. After 2012, Trabzon was one city where foreigners mostly bought homes. This study determines the effects of the second housing demand of foreigners on the social and economic structure of cities through Trabzon. Two surveys were conducted with foreigners who own homes and construction companies that supply housing to them. The results show that the physical and social characteristics of the city have a positive effect on the second housing demands of Arabs. The willingness of local people to live in different areas with foreigners and increased house prices stand out among the negative effects. Urban actors should direct the housing demand of foreigners in a way that increases the positive effects and eliminates the negative ones.